Client's perception of factors contributing to project delay : case study of projects completion in Multimedia University - Nora, Maliza Mohd; Samsuddin, Nurshamimah; Sulaiman, Masri; Yusof, Aini Qamariah Mohd; Osman, Shahariah (School of Social Sciences, USM, 2017)
For a company to grow, the construction industry is one of the industry that plays a major role in the economy by giving contribution of employment opportunity and financial support. As globalization is concern, delays in the construction industry is a global phenomenon. Delay is defined as the extended time beyond completion date stated in a contract. Delays can be eliminated and minimized only when their causes or factors affecting delay are identified. This study presents findings of a survey aimed at identifying the most important causes of delays in construction projects from the viewpoint of clients in Multimedia University. This research focused on clients’s perception towards the factors contributing to project delay. There are six causes of delay were identified during the research. Based on the literature review, questionnaire is distributed to the respondents who are clients for Multimedia University and a total of 150 responses was set as the target based on the sample size. Top three common causes of delay been identified and with the used of SPSS, the results show significant relationship between the project delay and clients perceptions.